Manajemen Risiko Usahatani Cabai Rawit : Studi Kasus Di Kawasan Gunung Merapi - Putri, Suryani Eka; Krisnamurthi, Bayu; Tinaprilla, Netti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
Cayenne pepper (Capsicum frutescens L) is a horticultural commodity commonly grown by farmers in the Merapi mountain region. The productivity and price of cayenne pepper have fluctuated significantly in recent years, both at the national level and in the Merapi mountain region. This study aims to describe the types, sources, and levels of risk, analyze and assess risk management in cayenne pepper farming based on risk levels, risk mapping, and total household income analysis of cayenne pepper farmers in the Merapi mountain region. The sample consisted of 100 farmers selected through simple random sampling, criteria including being residents who have been farming cayenne pepper for 10 years in the Merapi mountain region, growing cayenne pepper in the area, making cayenne pepper the main commodity on their land, and farmers who have sources of income outside of farming or do not have sources of income outside of farming. Data analysis includes risk analysis, total household income analysis, and quantitative descriptive analysis. In the Pakem District, the values for production risk, price risk, and profit risk are 67%, 8%, and 120%, respectively. In the Dukun District, these values are 55%, 14%, and 240%, respectively. Finally, in the Selo District, the values are 45%, 7%, and 84%, respectively. The analysis of farmers' household income is divided into two categories: farmers who have income outside of farming and those who do not have income outside of farming in each district. The highest average total household income of Cayenne pepper farmers is in the Selo District, with an average monthly income of Rp. 4,903,512. Important considerations in agricultural risk management include providing insurance for cayenne pepper, developing markets, and diversifying land use.